Conversion of waste lignocellulose to furfural using sulfonated carbon microspheres as catalyst. (1st May 2020) - Li, Xiaoyun; Lu, Xuebin; Liang, Min; Xu, Rui; Yu, Zhihao; Duan, Bingyu; Lu, Lefu; Si, Chuanling
Graphical abstract: Highlights: The sulfonated carbon microspheres (CCoS) were prepared for furfural production. CCoS catalyst possesses mesoporous structures and Brønsted and Lewis acid sites. The high furfural yields (>70%) from xylose and lignocellulosic biomass were achieved. The SO3 H groups of CCoS catalyst improved the dehydration xylose to furfural. Abstract: Catalytic conversion of xylose and the hemicellulose fraction of waste biomass to furfural is important for the valorization of waste lignocellulose. Here, a clean and efficient catalytic system consisting of sulfonated carbon microspheres catalysts and γ-valerolactone was developed for the upgrading of xylose and waste lignocellulose to the furfural in one-pot. Sulfonated carbon microspheres (CCoS) with Brønsted and Lewis acid sites were prepared to yield furfural. The mesoporous structures were facilitated by introduction of Co element in xylose hydrothermal process, and the density of Brønsted acid sites were improved by the sulfonation. The furfural yield from xylose reached 75.12% using CCoS as catalyst at 170 °C for 30 min in a γ-valerolactone/water (17/3 v/v) solvent. As typical Brønsted acid, the SO3 H groups on the surface of CCoS catalyst is essential for catalytic dehydration xylose to furfural. Additionally, the mesoporous structures of CCoS improved the mass transfer in the furfural production process. The catalytic system was applied in the conversion of real biomass (including corncob, corn straw and Eucalyptus sawdust) to evaluate the possibility of application. These three biomass species all reached excellent furfural yields, which were more than 70%. This work provided a catalytic strategy for effective conversion of xylose and biomass to furfural.